2011
DOI: 10.1002/jaal.00037
|View full text |Cite
|
Sign up to set email alerts
|

From Resistance to Advocacy for Math Literacy: One Teacher's Literacy Identity Transformation

Abstract: Secondary preservice teachers often articulate the belief that literacy instruction is irrelevant in their future content‐area classrooms. Resistance is not a new concern in literacy teacher education programs, but the longevity of this belief and the absence of content area literacy instruction in the majority of secondary classrooms are distressing realities. This article documents one math teacher's initial negative beliefs about literacy instruction and his teacher literacy identity transformation to openl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Each instructor felt that he or she had gained something from the project. Our findings agree with Spitler (), who suggested that the main actors must be involved for change to occur. Nonetheless, for some teachers, such as Jonah, the change was subtle.…”
Section: Looking Across the Disciplinessupporting
confidence: 93%
“…Each instructor felt that he or she had gained something from the project. Our findings agree with Spitler (), who suggested that the main actors must be involved for change to occur. Nonetheless, for some teachers, such as Jonah, the change was subtle.…”
Section: Looking Across the Disciplinessupporting
confidence: 93%
“…Although the role of disciplinary reading is thoroughly documented in subject areas such as science, mathematics, English language arts, and history (Ford and Forman 2006; Rainey and Moje 2012;Spitler 2011;Wineburg and Reisman 2015), disciplinary reading in RE, and in particular the role of the reader in meaning-making processes, is in need of further exploration. We use a disciplinary literacy perspective to explore how teachers and students make sense of reading in non-confessional RE.…”
Section: Disciplinary Literacy In Rementioning
confidence: 99%
“…Literacy-related coursework is designed to increase pre-service teachers' knowledge regarding its importance, expose them to a variety of literacy strategies, and improve attitudes and beliefs concerning literacy's role in the content area classroom. Given time and support, it is possible to change teacher attitudes (Hall, 2005;Spitler, 2011) and literacy-related coursework provides the necessary structure. To create in-service agriculture teachers who incorporate literacy skill development, we must begin to understand and change preservice teachers' attitudes and perceptions (Spitler, 2011).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%